2011
DOI: 10.1096/fj.11-187856
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin1/γ‐secretase promotes the EphB2‐induced phosphorylation of ephrinB2 by regulating phosphoprotein associated with glycosphingolipid‐enriched microdomains/Csk binding protein

Abstract: Reverse signaling through the ephrinB ligands is important for several morphogenetic events, such as axon guidance, neuronal plasticity, spine maturation, and synaptogenesis. Signaling is initiated by binding of EphB receptors to ephrinB ligands, stimulating their tyrosine phosphorylation via an unclear mechanism. Here we show that this mechanism involves presenilin1 (PS1)/γ-secretase regulation of phosphoprotein associated with glycosphingolipid-enriched microdomains/Csk binding protein (PAG/Cbp), an adaptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
(78 reference statements)
1
23
0
Order By: Relevance
“…This specific tyrosine phosphorylation site has been described to activate downstream Src family or associated kinases as a result of active ephrin B reverse signaling (Palmer et al, 2002;Wu et al, 2011;Georgakopoulos et al, 2011). In the wild type, we found phospho-specific staining in membranes of epithelial cells of the ND, the cloaca and endothelial cells at E10.5, whereas strongly reduced phospho-specific staining was detectable in the ND and the cloaca in the DKO situation (Fig.…”
Section: Cellular Changes In the Distal Nd Of Dko Embryossupporting
confidence: 51%
“…This specific tyrosine phosphorylation site has been described to activate downstream Src family or associated kinases as a result of active ephrin B reverse signaling (Palmer et al, 2002;Wu et al, 2011;Georgakopoulos et al, 2011). In the wild type, we found phospho-specific staining in membranes of epithelial cells of the ND, the cloaca and endothelial cells at E10.5, whereas strongly reduced phospho-specific staining was detectable in the ND and the cloaca in the DKO situation (Fig.…”
Section: Cellular Changes In the Distal Nd Of Dko Embryossupporting
confidence: 51%
“…ADAM10 is a prime example, where regulation likely occurs at multiple levels. Thus formation of a ligand-receptor complex across cell-cell junctions enables recognition by the ADAM10 substrate-binding domain, while the ensuing receptor activation likely leads to conformational changes in both Eph EphB-stimulated metalloprotease/ g-secretase sequential cleavage, controlling cytoskeletal changes in neural cells 98,124 Ephrin-B and calcium/NMDA activation promotes distinct ectodomain/ g-secretase cleavage events in neural cells 106 Contributes to the formation and maintenance of dentritic spines via activation of the Rac signaling pathway 133 Serine proteases RHBDL2 ephrin-B3 Exogenous co-expression degrades ephrin, physiological relevance unclear 142 Neuropsin EphB2…”
Section: Resultsmentioning
confidence: 99%
“…98 A later study showed involvement of the Csk binding protein (PAG/Cbp), an adaptor protein that controls the activity of Src kinases. 124 Ephrin-B2-soluble CTF2 forms a complex with PAG/Cbp promoting Src activation, 124 which in other contexts has been shown to control various cellular events such as cell proliferation, survival, and migration 125 most likely via remodelling of the actin cystoskeleton 126 ( Fig. 4A; Table 1).…”
Section: Regulated Intramembrane Proteolysismentioning
confidence: 99%
See 1 more Smart Citation
“…This type of regulated intramembranous proteolysis (RIP) has previously been demonstrated for ephrin-B2 (Georgakopoulos et al 2006), and later also for EphB2 (Litterst et al 2007;Xu et al 2009) and EphA4 (Inoue et al 2009). The γ-secretase mediated cleavage of ephrin-B2 upon EphB2 receptor binding regulates activity of Src in murine embryonic fibroblasts (MEF) (Georgakopoulos et al 2011;Waschbusch et al 2009). …”
Section: Introductionmentioning
confidence: 99%